An Effective Process for Simultaneous Extraction of Valuable metals (V, Cr, Ti, Fe, Mn) from Vanadium Slag using Acidic Sodium Chlorate Solution at the Water Bath Condition - liu, shiyuan; shen, shaobo; Chou, Kuo-Chih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
In the present work, a novel process for effective extraction of valuable metals (V, Cr, Ti, Mn, Fe, Al, and Mg) from the vanadium slag is proposed. The leaching parameters for valuable metals extraction from the vanadium slag by acidic sodium chlorate solution were studied to obtain conditions that vanadium can be leached without using a pyro metallurgical step since the roasting process requires high energy consumption. The optimal H2SO4 concentration, weight ratio of NaClO3 to sample, leaching time, leaching temperature, agitation speed and ratio of liquid volume to solid mass  were 6M, 0.2, 6h, 95℃, 200rpm and 10, respectively. Under these optimal conditions, the extraction ratio of vanadium and valuable metals (V, Cr, Ti, Mn, Fe, Al, and Mg) were 85.8 and 91.2%, respectively. Compared with salt roasting, valuable metals leaching by this method was very effective. Moreover, the temperature was low at the water bath condition.